RETRACTED ARTICLE: Fe3O4@SiO2-PMA-Cu magnetic nanoparticles as a novel catalyst for green synthesis of β-thiol-1,4-disubstituted-1,2,3-triazoles - Ronak Eisavi; Fereshteh Ahmadi (Scientific Reports)
Abstract The magnetic nanoparticles of Fe3O4 were synthesized through a solid-state reaction of hydrated iron (III) chloride, hydrated iron (II) chloride and NaOH, and then purified by calcination at high temperature. In order to protect ferrite nanoparticles from oxidation and agglomeration, and to manufacture a novel catalytic system of anchored copper on the magnetic substrate, the Fe3O4 was core-shelled by adding tetraethyl orthosilicate. Next, the prepared Fe3O4@SiO2 was supported by phosphomolybdic acid (PMA) as the second layer of nanocomposite at 80 °C in 30 h. Eventually, the new nanocomposite of Fe3O4@SiO2-PMA-Cu was successfully synthesized by adding copper (II) chloride solution and solid potassium borohydride. The structure of magnetic nanocatalyst was acknowledged through different techniques such as EDS, VSM, XRD, TEM, FT-IR, XPS, TGA, BET and FESEM. The synthesis of β-thiolo/benzyl-1,2,3-triazoles from various thiiranes, terminal alkynes and sodium azide was catalyzed by Fe3O4@SiO2-PMA-Cu nanocomposite in aqueous medium. In order to obtain the optimum condition, the effects of reaction time, temperature, catalyst amount and solvent were gauged. The recycled catalyst was used for several consecutive runs without any loss of activity.